THE INFLUENCE OF SERVICE QUALITY AND CLEAN WATER PRODUCT QUALITY ON CUSTOMER SATISFACTION AT PDAM TIRTA JENEBERANG GOWA DISTRICT - wahyuni, Wahyuni; Andi Mappatompo; Syarthini Indrayani (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the effect of service quality and clean water product quality on customer satisfaction at PDAM Tirta Jeneberang, Gowa Regency. The research method used is quantitative with a descriptive approach. The research location was carried out at PDAM Tirta Jeneberang, Gowa Regency, over a 3 month period. Data was collected through questionnaires and analyzed using descriptive statistical methods through applicationsStatistical Package for the Social Science (SPSS) 27. The results obtained from this research show that service quality (X1) and clean water product quality (X2) have a positive and significant effect on customer satisfaction